PENERAPAN REKAYASA TEKNOLOGI DTS THERAPY UNTUK MENURUNKAN TINGKAT KECEMASAN LANJUT - M Irhash Erlangga; Tukino; Dede Kuswanda (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2022)
Anxiety experienced by the elderly must be overcome, because it has the potential the physical, psychological, and behavioral. If it lasts intensively for a long time, it can lead to fatigue and even death. One way to overcome the issue of anxiety is through therapy. The elderly need a form of therapy that suits their needs. Therefore, it is necessary to specifically develop a therapeutic method that is comfortable, effective, and easy to do. This study aims to determine the results of the application of DTS Therapy on the level of anxiety in the elderly. The research design used Single Subject Research (SSR) with an A-B-A reversal design. The data collection tool used the Hamilton Anxiety Rating Scale (HARS) and the target behavior observation instrument which was prepared by the researcher based on the HARS scale. The type of therapy used is DTS Therapy which combines three therapeutic techniques, namely Deep Breathing, Thought Stopping and Spiritual Therapy. The research subjects are the elderly who live in Harapan Jaya Village, Bogor Regency. The target behavior observed was shortness of breath, raised voice, and easily startled. The results showed that the level of anxiety in the elderly decreased after receiving DTS Therapy. The implementation of DTS Therapy shows that DTS Therapy is a therapy that easy to understand and can be done independently by the elderly. DTS Therapy is recommended as a therapy to treat anxiety in the elderly.